PERLINDUNGAN HUKUM BAGI PEKERJA PARUH WAKTU UNTUK MENDAPATKAN HAK CUTI TAHUNAN - Bahari, Cornelia Indira Kusuma; Rusdiana, Emmilia (Universitas Negeri Surabaya, 2022)
Part-time workers are workers who work only part of the time from the normal working hours.Provisions for working time are contained in Article 77 of the Labor Law jo. UU no. 6 of 2023, namely 7 hours/day for 6 days or 8 hours/day for 5 days. Part-time workers are not mentioned in any law.The purpose of this research is to analyze the proper arrangements for Part-Time Workers to obtain annual leave rights and legal protection measures that can be given to Part-Time Workers. The research method uses normative juridical research. The writing approach uses a statutory approach by dissecting legal materials collected by means of literature studies which are analyzed prescriptively,as well as a conceptual approach that refers to legal doctrines as well as the views of experts. Based on the results of the study,the criteria for the type of work of Part-Time Workers have similarities so that the rights and obligations for Part-Time Workers can use the provisions in accordance with the Specific Time Work Agreement (PKWT). Regarding the protection of workers' basic rights, in this case the right to annual leave can be given to Part-Time Workers in proportion to the length of service. As for the legal protection that can be given to part-time workers,it is necessary to realize it in the form of a clear legal basis by ratifying the Geneva Convention and implementing it in Indonesia in the form of adding substance to PP 35 of 2021 as a type of work derived from PKWT.